The Inherent Desire to Learn: Intrinsically Motivating First Grade Students - Lara Hansen (Networks: An Online Journal for Teacher Research, 2001)
It was a simple question, innocently asked by one of my first grade students that served as the inspiration and motivation for this study. My class was preparing to begin a project for a math unit. After I explained and discussed the directions, guidelines, and expectations for this project, Kate raised her hand and asked, "What do we get when we are done?" Acting confused (in reality I was not-- I knew exactly what she meant) I asked her to explain the meaning behind her question. Quite matter-of-factly she went on to make clear that she was simply curious as to whether or not the class would be rewarded for doing this particular activity. Although innocent, Kate's question immediately burdened me with feelings of inadequacy. If my students felt they needed to be bribed with rewards to complete required class work, then I clearly lacked the skills required to motivate them. It was this event that spurred my attempt to figure out how to intrinsically motivate my students. I was determined that, if I could find this information, I would commit myself to applying whatever strategies or techniques were recommended in order to create an environment where my students could write, read, create, solve, question, and grow -- all for the love of learning.